2016
DOI: 10.1016/j.drugalcdep.2016.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for substance use disorders: A systematic review and meta-analysis

Abstract: Available evidence suggests no consistent differences between acupuncture and comparators for substance use. Results in favor of acupuncture for withdrawal/craving and anxiety symptoms are limited by low quality bodies of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…Despite several methodological differences, the studies indicated a positive effect of acupuncture treatment on alcohol-related symptoms and behaviors. Our results are partly consistent with findings of a recent meta-analysis that observed a significant difference between acupuncture and control conditions in terms of reducing postintervention withdrawal/craving and anxiety in patients with a substance use disorder [ 8 ]. Interestingly, this prior meta-analysis also showed that acupuncture had unique effects on some variables on alcohol use disorder such as treatment dropout.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Despite several methodological differences, the studies indicated a positive effect of acupuncture treatment on alcohol-related symptoms and behaviors. Our results are partly consistent with findings of a recent meta-analysis that observed a significant difference between acupuncture and control conditions in terms of reducing postintervention withdrawal/craving and anxiety in patients with a substance use disorder [ 8 ]. Interestingly, this prior meta-analysis also showed that acupuncture had unique effects on some variables on alcohol use disorder such as treatment dropout.…”
Section: Discussionsupporting
confidence: 92%
“…A five-point auricular protocol was developed by the National Acupuncture Detoxification Association in the 1980s, and a body point electrical stimulation protocol was designed by a Chinese doctor in the 1990s [ 7 ]. Researchers have attempted to elucidate the therapeutic effects of acupuncture on reducing addiction-related symptoms and regulating brain dysfunction using various treatment protocols [ 8 , 9 ]. Despite methodological differences in acupuncture points, treatment durations, and types of control conditions among studies [ 9 ], a recent meta-analysis study demonstrated a significant beneficial effect of acupuncture on addiction-related clinical symptoms, such as withdrawal/craving and anxiety, with a medium to large effect size, although the data were heterogeneous and had a significant publication bias [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the key success factors of occupational health and safety were determined on the basis of a systematic review of the existing literature. Studies were independently selected in accordance with the PICO inclusion and exclusion criteria [41].…”
Section: Discussionmentioning
confidence: 99%
“…Third, they did not present results related to an essential treatment outcome in SUDs that refer to the attrition rate (AR) [53]; also, they did not take into consideration several other secondary outcomes that are robustly associated with relapse in substance use among clinical populations (i.e., negative affectivity, depressive/anxiety and post-traumatic symptoms and avoidance coping strate-fulness", "mindfulness meditation," "MBI," "mindfulness training", "MBSR," "mindfulness-based cognitive therapy," "MBRP," "dialectical behavior therapy," "ACT," "spiritual self-schema therapy," "Vipassana meditation," and "Zen meditation" in combination with the name of each substance (i.e., substances, drugs, alcohol, marijuana, cocaine, opioid, heroin, methamphetamine). The references of reviews and meta-analyses were referred to as additional sources of information [49][50][51][61][62][63].…”
Section: Doi: 101159/000490762mentioning
confidence: 99%